Novel Synthetic Approaches For The Synthesis Of Antipsychotic Drug Olanzapine - CHANDRA SEKHAR BVVN,; RAMESH KUMAR N,; CHAKRAVARTHY A,; MUKKANTI K, (International Journal of Pharma and Bio Sciences, 2011)
The present work is relatd to novel synthetic approaches for the synthesis of antipsychotic drug, Olanzapine. The present work is related to two novel approaches for the synthesis of olanzapine and an improved process for the synthesis of olanzapine. The present work is also related to identification, synthesis and characterization of process related impurities of olanzapine.